Pengembangan Stateful Packet Inspection dengan Metode NDPMon untuk Duplicate Address Detection - Steven Urbani; Widhi Yahya; Eko Sakti Pramukantoro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Software defined networking is a new field of research, where the concept aims to replace an inflexible and complex network with an innovative and agile network by separating the control plane and data plane. One of the protocols that can carry the concept of SDN is OpenFlow. Problems about network security that related about gap on conventional network are also occur on the OpenFlow network. One of the network attacks which can be threatening the security of the OpenFlow network is DoS of duplicate address detection, which attackers exploit a gap on IPv6 duplication checking schemes in a local network. Program that can be applied on controller to resolve some security issues in OpenFlow is Stateful Packet Inspection. To resolving the gap, development of the Stateful Packet Inspection can be done to prevent attacks on duplicate address detection processes by adding an NDP checking mechanism using the NDPMon method. There are several tests to test the system's functionality and performance in overcoming gaps in DAD process on the OpenFlow network. From the test results, we obtained that the system can noticed duplicate address detection process and successed to handle three test scenarios for DAD DoS attacks.